Personalized Nutrition in Food Allergy: Tips for Clinical Practice - D'Auria, Enza; Pendezza, Erica; Zuccotti, Gian Vincenzo (Frontiers in Pediatrics, 2020)
Nowadays, food allergies are considered as a spectrum of a variety of disorders that need different approaches. The “one size fits all” approach is giving way to a “targeted approach”, based on the identification of the patient’s phenotype. Thus, the approach to the nutritional management of food allergy has moved on from simply being “yes or not” to “how much, “in which form” and “for which patients”. Different factors should be considered to make a patient-tailored nutritional plan in clinical practice. Tailored nutritional plan may help to reduce the nutritional, social and economic burden of food allergy.